Studies on Vietnamese language and literature : a preliminary bibliography - Nguyẽ̂n, Đình Thâm, 1940- (Southeast Asia Program, Cornell University, 1992)
This work contains over 2,500 entries to guide students and scholars interested in the languages and literature of Vietnam. The books, monographs, and journal articles considered are those written in the Western languages (especially French and English). Meticulously researched and indexed, this bibliography is both the first of its kind and an invaluable reference tool.